2012
DOI: 10.1099/ijs.0.026740-0
|View full text |Cite
|
Sign up to set email alerts
|

Emended descriptions of Bacillus sporothermodurans and Bacillus oleronius with the inclusion of dairy farm isolates of both species

Abstract: Bacillus sporothermodurans is an industrially important micro-organism because of its ability to produce endospores which resist ultra high temperature (UHT) and industrial sterilization processes. It was described by Pettersson et al. (1996) based on seven genetically homogeneous isolates all from UHT-milk. Bacillus oleronius, the closest phylogenetic neighbor of B. sporothermodurans, was described by Kuhnigk et al. (1995), based on a single strain, isolated from the hindgut of the termite Reticulitermes sant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…After growth on TSYEB, the macroscopic examination of the isolate under wet mount revealed motile rods, single or in pairs (Supplementary video 5). This observation is in agreement with the findings of Kuhnigk et al (1995), but in contrast with Heyndrickx et al (2012) who reported B. oleronius as being non-motile. The Gram reaction of the isolate was not easy to score.…”
Section: Bacillus Licheniformissupporting
confidence: 92%
See 1 more Smart Citation
“…After growth on TSYEB, the macroscopic examination of the isolate under wet mount revealed motile rods, single or in pairs (Supplementary video 5). This observation is in agreement with the findings of Kuhnigk et al (1995), but in contrast with Heyndrickx et al (2012) who reported B. oleronius as being non-motile. The Gram reaction of the isolate was not easy to score.…”
Section: Bacillus Licheniformissupporting
confidence: 92%
“…The isolate was reported to be esculin-positive and stained Gram-negative (Kuhnigk et al, 1995). Subsequently, the organism has been isolated from additional sources including animal feed (Vaerewijck et al, 2001), cow-teat skin (Verdier-Metz et al, 2012) and raw milk (Heyndrickx et al, 2012).…”
Section: Bacillus Licheniformismentioning
confidence: 99%
“…B. cereus can contaminate milk and dairy products with very low infective dose of 10 3 -10 4 bacterial cells/g, the heating process in pasteurization is insufficient to eliminate all spores, the psychrotrophic nature of the spores allows them to thrive in cold environments, and the long appendages on the surface of the spores permits great adherence. Spores are capable of adhering to the big vessels, pipelines and tanks used in dairy industries, thus allowing them to persist during routine cleaning procedures [4] [10]. Treating these endospores is usually more difficult due to their properties of heat and antimicrobial chemical resistant [11].…”
mentioning
confidence: 99%
“… Bacillus thermoamylovorans DKP T (Combet‐Blanc et al., ), Bacillus thermolactis R‐6488 T (Coorevits et al., ), Bacillus smithii NRRL NRS‐173 T (Bae, Lee, & Kim, ), Bacillus aquimaris TF‐12 T (Yoon, Kim, Kang, Oh, & Park, ), Bacillus sporothermodurans M215 T (Heyndrickx et al., ), Bacillus acidicola 105‐2 T (Albert, ), Bacillus alveayuensis TM1 T (Bae et al., ), and Bacillus coagulans 2‐6 T (De Clerck et al., ). …”
Section: Resultsmentioning
confidence: 99%